2019
DOI: 10.1016/j.ipej.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of catheter ablation for atrial fibrillation in congenital heart disease – A systematic review and meta-analysis

Abstract: BackgroundPrevalence of atrial fibrillation (AF) in patients with congenital heart disease (CHD) is on the rise. Anti-arrhythmic drugs are usually the first line of treatment in CHD, however, it is often ineffective and poorly tolerated. We aimed to perform a systematic review to assess the efficacy and safety of catheter ablation for AF in CHD.MethodsWe performed a comprehensive search on catheter ablation for atrial fibrillation in congenital heart disease up until July 2019 through several electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Clinical data support that transseptal access through the device is safe and efficacious, 54 , 60 , 61 , 62 , 63 , 64 with success rates comparable with those described in patients in whom access was gained through the native septum. 54 , 59 , 65 However, to avoid potential septal spit or device dislodgement in the process of penetrating the device, 63 an upsized dilator may be used to dilate the puncture site and enable the sheath to go through the device.…”
Section: Achd Forms Treated With Af Ablationmentioning
confidence: 57%
See 1 more Smart Citation
“…Clinical data support that transseptal access through the device is safe and efficacious, 54 , 60 , 61 , 62 , 63 , 64 with success rates comparable with those described in patients in whom access was gained through the native septum. 54 , 59 , 65 However, to avoid potential septal spit or device dislodgement in the process of penetrating the device, 63 an upsized dilator may be used to dilate the puncture site and enable the sheath to go through the device.…”
Section: Achd Forms Treated With Af Ablationmentioning
confidence: 57%
“… 38 , 40 , 42 , 43 , 44 , 51 , 52 , 54 , 59 , 63 , 92 , 93 , 94 , 95 , 96 , 97 Notably, the procedure seems to be more effective in patients with ASD. 64 However, the AF recurrence rate is high, reaching up to 56.1% in previous studies ( Table ); therefore, repeated ablation attempts may be needed to manage AF. Anatomic complexity, persistent AF pattern, and left atrial size have been proposed as independent predictors of arrhythmia recurrence after AF catheter ablation.…”
Section: Achd Forms Treated With Af Ablationmentioning
confidence: 96%
“…In the current era, the correlation between the success rates of AF ablation and the complexity of CHD remains a controversial issue. The ablation of atrial septal defects seems to have the highest success rates [25]. A meta-analysis published at 2019 by Pranata R. et al showed no great differences between simple-moderate and complex CHD, with the latter needing more advanced equipment and being performed by experts in tertiary centers [25].…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…AF is the most prevalent severe abnormal heart rhythm associated with a fast heart rate. It refers to an abnormal, rapid, and non-synchronized muscle fiber contraction with complex patophysiology [4][5][6][7], and is recognized as an independent risk factor for stroke, with important clinical and economic consequences. Diagnosing the symptoms is important before treatment of this severe disease; however, existing commercial ECG devices for AF detection methods still show actual misdiagnosis rates.…”
Section: Introductionmentioning
confidence: 99%